PERBAIKAN KUALITAS PRODUK WAJAN DENGAN MENGGUNAKAN METODE SIX SIGMA DAN KANO - Teguh Yulianto; Ari Zaqi Alfaritsy (Jurnal Ilmiah Teknik Industri, 2015)
PT. "X" is a company engaged in the aluminum foundry industry. Pan is a product that every day is produced by the company PT. "X. This study determines the characteristics of the products that customers want and reduce the presence of defective products in the manufacture of the skillet to the improvement of product quality. Research methods is DMAI in six sigma method as measures to improve product quality pan. The characteristics of the products that customers want is a thick pan. Customer satisfaction PT. "X" is met with production pans that do not have a big hole, a small hole, and the line - the line broke on the surface of the pan so that the consumption or use of the pan into a durable. Sigma level of PT. "X" amounting to 2,785 sigma which means it is still far from the level of six sigma. Improvements to minimize the occurrence of defects porous product skillet needs to be done on the operator that the process of entering the liquid aluminum into a mold to be in a state of fluid color pink, raw materials that take the raw materials that do not melt before the liquid aluminum inserted into a mold and method of production process pan  namely the application of whitewash is done evenly to all parts of the upper surface of the mold.